Perioperative evaluation of tumescent anaesthesia technique in bitches submitted to unilateral mastectomy - Credie, Leonardo de Freitas Guimaraes Arcoverde [UNESP] (2013)
Background: Tumescent anaesthesia (TA) is a widely used technique in oncologic surgeries necessitating large resection margins. This technique produces transoperative and postoperative analgesia, reduces surgical bleeding, and facilitates tissue divulsion. This prospective, randomised, blind study evaluated the use of TA in bitches submitted to mastectomy and compared the effect of TA with an intravenous fentanyl bolus. A 2.5-mcg/kg intravenous fentanyl bolus (n = 10) was compared with TA using 0.275% lidocaine (n = 10) in bitches submitted to unilateral mastectomy. Sedation was performed by intramuscular (IM) injection of 0.05 mg/kg of acepromazine combined with 2 mg/kg of meperidine. Anaesthesia was induced with 5 mg/kg of intravenous propofol and maintained with isoflurane/O2. Heart and respiratory rates; systolic, mean, and diastolic arterial blood pressures; central venous pressure; SpO2; ETCO2; inspired and expired isoflurane concentrations; and temperature were measured transoperatively. Visual analogue scales for sedation and pain and the Glasgow composite and Melbourne pain scales were used for postoperative assessment. The surgeon investigated the quality of the surgical approach, considering bleeding and resection ability, and the incidence of postoperative wound complications.Results: The heart rate was lower and the end-tidal isoflurane concentration was higher in dogs treated with fentanyl than in dogs treated with TA. A fentanyl bolus was administered to 8 of 10 dogs treated with fentanyl and to none treated with TA. Intraoperative bleeding and the mammary gland excision time were lower in dogs treated with TA. The maximal mean and individual plasma lidocaine concentrations were 1426 ± 502 ng/ml and 2443 ng/ml at 90 minutes after infiltration, respectively. The Glasgow Composite Pain Scale scores were higher in dogs treated with fentanyl than in dogs treated with TA until 2 hours after extubation.Conclusions: Compared with intravenous fentanyl, TA in bitches: may be easily performed in non-inflamed, ulcerated, adhered mammary tumours; has an isoflurane-sparing effect; improves transoperative and immediate postoperative analgesia; is apparently safe for use in clinical conditions as evidenced by the fact that it did not produce any adverse signs or lidocaine plasma concentrations compatible with toxicity; does not modify the recovery time; and facilitates the surgical procedure without interfering with wound healing. © 2013 Credie et al.; licensee BioMed Central Ltd.